Stability improvement and control optimization of isolated two-stage AC-DC-DC converter systems - Feng, Fan (Nanyang Technological University, 2020)
Driven by the ever-increasing energy demand and the desire for carbon footprint reduction, the power industry is under a wave of transformation from the current grid into the smart grid. As the trend of the grid transformation continues, a significantly high penetration level of renewable energy resources, in parallel with other emerging technologies such as the energy storage and electric vehicles, is to be expected. Since many types of renewables and energy storage devices, e.g., solar photovoltaic, batteries and supercapacitors, etc., are treated as DC sources, the multi-stage converter system is usually employed as the interface between the AC grid and DC networks. Specifically, the dual active bridge (DAB)-based two-stage AC-DC-DC converter is highly related to the distributed systems because of its advantages such as the high power density, soft switching properties, galvanic isolation and less passive components. Therefore, the stability and reliability of the two-stage AC-DC-DC converters are at the core of the distributed system operations. However, despite its control benefits, the two-stage AC-DC-DC converter system may suffer instability issues. This thesis aims to investigate and overcome the instability issues of the two-stage AC-DC-DC converter system.